On a collection of caridean shrimps (Decapoda, Caridea) from St. Helena, south-central Atlantic, with further records from Ascension Island - De Grave, Sammy (2019)
We report on a recent collection of caridean shrimps from St. Helena in the south-central Atlantic Ocean, raising the total number of species known from the island to 24. Six species are newly recorded for the area, with no endemic species present. Additional three species are recorded from Ascension Island. A close biogeographical connection between the caridean faunas of St. Helena and Ascension Island is evident.